Pengaruh pemberian nanoenkapsulasi ekstrak buah senduduk (Melastoma malabathricum L.) terhadap kinerja pertumbuhan ayam broiler - Muhammad Dani; Rusman; Zuprizal (Jurnal Ilmu Peternakan Terapan, 2022)
The aim of this research was to examine the impact of nano encapsulation of Melastoma malabathricum L. fruit extract as feed additive that was given through drinking water towards growth performance of broiler. Experimentation plan that used in this research were completely randomized design using 6 increment treatment of Melastoma malabathricum L. fruit extract to the drinking water of the chicken each with 5 repetitions. Detail of rations treatment were T0 drinking water treatment without feed additive (negative control), T1 drinking water treatment + 0.2 mg/kg body weight simvastatin (positive control), T2 drinking water treatment + 1.5% Melastoma malabathricum L. fruit extract, T3 drinking water treatment + 3.0% Melastoma malabathricum L. fruit extract, T4 drinking water treatment + 1.5% nano-encapsulation of Melastoma malabathricum L. fruit extract, T5 drinking water treatment + 3.0% nano-encapsulation of Melastoma malabathricum L. fruit extract. Parameters observed were the nano-encapsulation characterization of Melastoma malabathricum L. fruit extract (particle size, potential zeta, and morphology), growth performance of broiler: feed intake, body weight, and FCR. The result of this research showed adding the nano-encapsulation of Melastoma malabathricum L. fruit extract do not give impact toward growth performance.